Acquisition and Loss of Nationality|Volume 1: Comparative Analyses Policies and Trends in 15 European Countries - Groenendijk, Kees; Ersbøll, Eva; Waldrauch, Harald; Bauböck, Rainer (Amsterdam University Press, 2006)
Nationality and citizenship have been subjects of stormy policy debates in many EU countries in recent years. Concerns over the integration of immigrants, but also attempts to forge links with emigrants, have led to changes in the laws regulating loss and acquisition of nationality and citizenship. This title outlines the research conducted by a team of 30 researchers into the nationality laws and their implementation in 15 EU member states. Acquisition and Loss of Nationality - Volume 1 presents the results of a systematic comparative analysis. It uses a novel methodology that permits a detailed comparison how nationality can be acquired or lost across all 15 countries. The results show divergent trends towards liberalization in some countries and new restrictions of access to nationality in others. The book examines the impact of international and European law, presents statistical data on naturalization and assesses administrative practices. Although the European Union has no formal competence in regulating nationality, the nationality laws of member states are linked to each other via the common citizenship of the Union. Member States should therefore agree on common norms for their nationality laws. The book contains detailed policy recommendations based on the idea that stakeholders in the political community should be given access to nationality. Studies of each country's nationality law are published separately in "http://www.aup.nl/do.php?a=show_visitor_book&isbn=9789053569214"> Volume 2. Additional material including detailed statistics and further comparative analyses of legal regulations of nationality is available at "http://www.imiscoe.org">www.imiscoe.org. Volume 1 & 2 are also available as a set, "http://www.aup.nl/do.php?a=show_visitor_book&isbn=9789053569498&l=2">click here for more information. This is the most comprehensive comparative study of the legal status of nationality so far and it will become an indispensable source of reference for further research. For more information see: "http://www.imiscoe.org/natac/">http://www.imiscoe.org/natac/